Analysis of judicial and pharmaceutical practice concerning falsification of medicines and circulation of counterfeit medicines - Панькевич, Остап Богданович; Громовик, Богдан Петрович (ScienceRise: Pharmaceutical Science, 2016)
Aim. The aim of our research was analysis of judicial and pharmaceutical practice concerning falsification of medicines in Ukraine in terms of effective implementation of Council of Europe Convention “On the counterfeiting of medical products and similar crimes involving threats to public health”. Methods. Legal analysis method, including doctrinal analysis of theoretical and practical issues of appropriate law areas, as well as official responses of judicial and law enforcement authorities, was used for research. Results. Detailed analysis of judicial and pharmaceutical practice concerning falsification of medicines in Ukraine during 2015 year was carried out. The regulatory framework and response letters of executive and judicial authorities were processed, that allowed setting efficiency of the enforcement practices concerning criminal offenses specified in Article 321-1 of the Criminal Code of Ukraine Falsification of medicines and circulation of counterfeit medicines. Conclusion. The enforcement practices concerning criminal offenses specified in Article 321-1 of the Criminal Code of Ukraine Falsification of medicines and circulation of counterfeit medicines was summarized and systematized for the first time. It was found, that in 2015, 9 persons were sentenced for criminal offenses specified in Article 321-1 of the Criminal Code of Ukraine, and under preliminary investigation for this article more than a third part of criminal proceedings were closed. Thus, during 2015, about 70 letters concerning falsification of medicines cases and/or illegal trade of medicines via Internet were sent by the State Service of Ukraine on Drugs